Carbonized Cow Dung as a High Performance and Low Cost Anode Material for Bioelectrochemical Systems - Feng, Huajun; Ge, Zhipeng; Chen, Wei; Wang, Jing; Shen, Dongsheng; Jia, Yufeng; Qiao, Hua; Ying, Xianbin; Zhang, Xueqin; Wang, Meizhen (Frontiers in Microbiology, 2018)
We develop a high-performance anode formed from carbonized cow dung for bioelectrochemical systems. Thermal gravimetric analysis showed that the CD carbonization process started at 300°C and ended at approximately 550°C; the weight was reduced by 51%. After a heat-treatment at 800°C for 2 h, the treated CD featured a good conductivity and a high specific surface area. The maximum current density of 11.74 ± 0.41 A m-2 was achieved by CD anode (heated at 800°C), which remained relatively stable from more than 10 days. This study shows that a valuable anode material can be produced through conversion of CD by high-temperature carbonization. This approach provides a new way to alleviate environmental problems associated with CD.